KEKONVERGENAN BARISAN INFINITESIMAL - Afriyani, Dona (IAIN Batusangkar, 2010)
This article was to find descript methode theory with number of Sequences. Base on theory has found the relationships it, are if has a free infestimal sequences line each other, then number of intestimal konvergencies with distribution of free variable in a function at conditions. Key words: infestimal sequences, convergen, characteristic of function